Substantiating the efficiency of using packaging with oxygen absorber when storing small-piece natural semi-finished meat products - Bal-Prylypko, Larysa; Serdyuk, Marina; Bandura, Valentyna; Drachuk, Uliana; Andrushchenko, Mykola; Shlapak, Halyna; Halukh, Bohdan; Kirovich, Natalia (Eastern-European Journal of Enterprise Technologies, 2025)
This study's object is the process of storing small-piece natural meat semi-finished products in packaging with an oxygen sorbent. The task addressed relates to determining the safe shelf life of the product without deterioration in quality indicators. The application of packaging with an oxygen sorbent could significantly prolong the shelf life of semi-finished products before their use. The dynamics of changes in the physicochemical, functional, and organoleptic indicators of the product during storage have been studied. The samples were packaged in barrier polymer packaging in two variants: control (without absorber) and experimental (with oxygen absorber). Storage was carried out at a temperature of minus 1…1°C for 14 days. The change in pH, water-holding capacity, transformation of the content of essential macronutrients and sensory characteristics was studied. It was found that beef retains moisture better than pork due to its lower fat content. In pork, on the contrary, high fat content leads to significant moisture loss, especially under normal storage conditions after 5–7 days. The use of an oxygen sorbent helps maintain a high moisture-holding capacity of meat for up to 14 days. It was shown that samples with sorbent demonstrated more stable, linear moisture retention, while control samples lost it much faster. Studies have shown a strong feedback between pH level and water-holding capacity, which makes it possible to predict changes in the latter. During the storage of meat semi-finished products without oxygen sorbent, a more intense decrease in protein was observed, a relative increase in fat due to dehydration with an increased risk of oxidation and accumulation of carbohydrates, while the use of sorbent helped restrain these negative changes. Thus, the use of oxygen absorbers in the composition of active packaging contributes to the preservation of physicochemical and sensory indicators of meat semi-finished products, reduces the intensity of oxidative processes, and extends their shelf life by 5–6 days without the use of preservatives. The results could be used for designing innovative packaging for chilled meat products